If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 5u + -34 = -8(u + 1) Reorder the terms: -34 + 5u = -8(u + 1) Reorder the terms: -34 + 5u = -8(1 + u) -34 + 5u = (1 * -8 + u * -8) -34 + 5u = (-8 + -8u) Solving -34 + 5u = -8 + -8u Solving for variable 'u'. Move all terms containing u to the left, all other terms to the right. Add '8u' to each side of the equation. -34 + 5u + 8u = -8 + -8u + 8u Combine like terms: 5u + 8u = 13u -34 + 13u = -8 + -8u + 8u Combine like terms: -8u + 8u = 0 -34 + 13u = -8 + 0 -34 + 13u = -8 Add '34' to each side of the equation. -34 + 34 + 13u = -8 + 34 Combine like terms: -34 + 34 = 0 0 + 13u = -8 + 34 13u = -8 + 34 Combine like terms: -8 + 34 = 26 13u = 26 Divide each side by '13'. u = 2 Simplifying u = 2
| 8x-8=62 | | 3x^2-12x=8-2x | | x(2x+-9)=45 | | -9/5-2/3u=-1/2 | | (X-2)=-1/4(x-8) | | 9x-3y=101 | | -2(x-4)+3(x+1)=17 | | 4n+4=34-2n | | 11g=66 | | N=-1.825 | | 6b+9h= | | (3x^2-6x-9)/(x-5) | | 2z/7-1=8 | | 28-4v=2v+4 | | -3x+17-5x=12-(6x+3) | | f(-49)=-5x+1 | | 3/4=7/x-9 | | 5x-2y+3x+y= | | -21=-9+4x | | 2x+10=5x+10-3x | | f(-2)=x^2-5 | | 8-2+a-9a= | | F(-2)=5x^2-7x+10 | | (4x+6)=(3x+9) | | (6-15)*(4+5)= | | 10x-2(x+4)=4x-7 | | 40+50m=365 | | x+x+89=180 | | 5+11p=71 | | 128=2(6y-2) | | -4x+5x=-16 | | 15+x=3*x-15 |